2007
DOI: 10.1029/2006gc001373
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control on serpentine crystallization in veins: Constraints on hydration processes in oceanic peridotites

Abstract: [1] Deformation and hydration processes are intimately linked in the oceanic lithosphere, but the feedbacks between them are still poorly understood, especially in ultramafic rocks where serpentinization results in a decrease of rock density that implies a volume increase and/or mass transfer. Serpentinization is accompanied by abundant veining marked by different generations of vein-filling serpentines with a high variety of morphologies and textures that correspond to different mechanisms and conditions of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(207 citation statements)
references
References 57 publications
12
194
0
1
Order By: Relevance
“…Andreani et al [74] described the kinetic control on serpentine vein mineralogy, with an overall chronological evolution from poorly crystalline protoserpentine to conical serpentine, chrysotile, polygonal serpentine, polyhedral serpentine and lizardite. According to these authors, the main serpentine veins found in natural faults and shear zones are (formed from the first to last stages of serpentinite evolution): isolated sigmoidal chrysotile veins (V2 in their classification); crack-seal veins formed by variable mixtures of protoserpentine, chrysotile and polygonal serpentine fibres (V3; see also [53] for this kind of vein); and polyhedral serpentine/lizardite veins (V4).…”
Section: The Role Of Serpentine Veinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andreani et al [74] described the kinetic control on serpentine vein mineralogy, with an overall chronological evolution from poorly crystalline protoserpentine to conical serpentine, chrysotile, polygonal serpentine, polyhedral serpentine and lizardite. According to these authors, the main serpentine veins found in natural faults and shear zones are (formed from the first to last stages of serpentinite evolution): isolated sigmoidal chrysotile veins (V2 in their classification); crack-seal veins formed by variable mixtures of protoserpentine, chrysotile and polygonal serpentine fibres (V3; see also [53] for this kind of vein); and polyhedral serpentine/lizardite veins (V4).…”
Section: The Role Of Serpentine Veinsmentioning
confidence: 99%
“…At the outcrop scale, fibrous serpentine veins (type V3 in [74]) and splintery antigorite veins represent the most commonly encountered vein types. These veins often constitute the typical anastomosing slickenfibre faults that surround lens-shaped massive blocks (e.g., Figure 3).…”
Section: The Role Of Serpentine Veinsmentioning
confidence: 99%
“…Research on detachment faulting and OCCs indicates that this style of oceanic spreading is intimately linked to hydrothermal circulation and encompasses a wide variety of fluid flow and hydrothermal regimes (McCaig et al, 2007). High-temperature fluid circulation is well documented mineralogically and geochemically (Schroeder and John, 2004;Boschi et al, 2006;McCaig et al, 2010), and uplift along detachments may promote circulation and alteration within the footwall (Andreani et al, 2007). McCaig et al (2007) propose temporal evolution in the style of hydrothermal circulation associated with the development of OCCs: from high-temperature systems hosted in the basaltic hanging wall within the rift valley (e.g., Trans-Atlantic Geotraverse [TAG]-type), to high-temperature ultramafic-hosted systems within the footwall (Rainbowtype), and ultimately to off-axis ultramafic-hosted systems within the footwall (Lost City-type).…”
Section: Iodp Proceedingsmentioning
confidence: 99%
“…At low-pressure conditions, formation of secondary olivine is expected at 380 °C, whereas secondary clinopyroxene appears at 450 °C in the system CaOMgO-SiO 2 -H 2 O (Fig. 13, Nozaka 2005; Andreani et al 2007;Plümper et al 2012 and references therein). If true, this confirms general low-grade metamorphic conditions for the BBM serpentinites, similarly to lithologies from other Central-Sudetic Ophiolites (Kryza and Pin 2010).…”
Section: Western Part Of the Braszowice-brzeźnica Massifmentioning
confidence: 99%